3 Tesla stack-of-stars echo unbalanced T1 relaxation-enhanced steady-state MRI for brain tumor imaging: post-contrast comparison with MPRAGE - Adrienn Tóth; Robert R. Edelman; Dmitrij Kravchenko; Justin A. Chetta; Jennifer Joyce; James Ira Griggers; Ruoxun Zi; Kai Tobias Block; M. Vittoria Spampinato; Akos Varga-Szemes (Cancer Imaging)
Abstract Background This study compared the image quality and diagnostic utility of stack-of-stars echo-unbalanced T1 relaxation-enhanced steady-state (SOS echo-uT1RESS) with the widely used magnetization-prepared rapid gradient-echo (MPRAGE) sequence in brain tumor imaging. Methods In this prospective, two-center observational study, each participant underwent 3T contrast-enhanced MRI of the brain with both standard MPRAGE and prototype SOS echo-uT1RESS sequences. Lesion size, contrast-to-noise ratio (CNR), and tumor-to-brain contrast were quantitatively analyzed. Overall image quality, lesion conspicuity, and image artifacts were scored on a 4-point Likert scale, while diagnostic performance and assessment of the vascular and dural involvement were compared side-by-side by three readers. Results Thirty-four adult patients (mean age, 64 years ± 13 [SD], 12 men) with known brain tumors (N = 6 intra-axial primary tumors; N = 14 intra-axial metastases; N = 14 extra-axial tumors) were enrolled in this study. There was no significant difference in CNR between MPRAGE and SOS echo-uT1RESS (29.4 ± 21.4 vs. 28.2 ± 16.5, respectively; p = 0.80, r = 0.03). SOS echo-uT1RESS demonstrated a 1.8-fold improvement in tumor-to-brain contrast compared with MPRAGE (0.7 ± 0.4 vs. 0.4 ± 0.3, respectively; p < 0.001, r = 0.81). While overall image quality and image artifacts were similar for both sequences, SOS echo-uT1RESS showed improved lesion conspicuity (p < 0.001, r = 0.51) and improved diagnostic performance (p < 0.001, r = 0.53), particularly for small metastases. Conclusion SOS echo-uT1RESS enhanced lesion visibility, achieving approximately a 1.8-fold improvement in tumor-to-brain contrast compared to MPRAGE, although this finding may reflect both sequence properties and timing-related effects. The sequence maintained comparable overall image quality and robustness, making it a promising tool for brain tumor imaging.